PEMANFAATAN PARTIER TEC-12706 SEBAGAI GENERATOR TERMAL ELEKTRIK PADA PROTOTIPE KINCIR ANGIN MINI DENGAN MOTOR DC 5V - Fitriyanti, Fitriyanti (SAINFIS: Jurnal Sains Fisika, 2024)
One of the alternative energy technologies that can be utilized as renewable energy is the utilization of thermoelectric generators. Besides its simple application, thermoelectric generators do not produce residues that can harm the environment, as their principle of operation is based on the temperature difference between two different heat sources, creating a flow of heat energy from the hotter source to the cooler one. Thermoelectric generators utilize thermoelectric devices, such as thermoelectric modules or thermocouples, which exploit the Seebeck effect to generate electricity. In this study, the Partier Tec-12706 was employed as a thermoelectric generator in a prototype of a mini wind turbine with a 5V DC motor. Through this research, a prototype of a thermoelectric generator was successfully designed and tested for the magnitude of temperature changes with the resulting power output. The study utilized a DC motor connected in series as a converter of electrical energy from the Partier TEC-12706 into mechanical energy capable of driving the mini wind turbine used in the research. The research findings indicate that the thermoelectric generator using Partier Tec-12706 can generate electrical power ranging from 3.92 to 6.4 watts. Furthermore, it is evident that the greater the change in heat value, the greater the power produced by the generator. Further testing demonstrates that the device can rotate a DC motor with a voltage of 3 to 6 volts, ultimately enabling the mini wind turbine in the prototype to rotate. These findings highlight the potential of utilizing Partier Tec-12706 as an effective thermoelectric generator in generating electrical energy from heat value changes, thus contributing to the development of environmentally friendly renewable energy technologies.